A Review on Metal-Organic Frameworks as Congenial Heterogeneous Catalysts for Potential Organic Transformations - Gangu, Kranthi Kumar; Jonnalagadda, Sreekantha B. (Frontiers in Chemistry, 2021)
Metal-organic frameworks (MOFs) have emerged as versatile candidates of interest in heterogeneous catalysis. Recent research and developments with MOFs positively endorse their role as catalysts in generating invaluable organic compounds. To harness the full potential of MOFs in value-added organic transformation, a comprehensive look at how these materials are likely to involve in the catalytic processes is essential. Mainstays of MOFs such as metal nodes, linkers, encapsulation materials, and enveloped structures tend to produce capable catalytic active sites that offer solutions to reduce human efforts in developing new organic reactions. The main advantages of choosing MOFs as reusable catalysts are the flexible and robust skeleton, regular porosity, high pore volume, and accessible synthesis accompanied with cost-effectiveness. As hosts for active metals, sole MOFs, modified MOFs, and MOFs have made remarkable advances as solid catalysts. The extensive exploration of the MOFs possibly led to their fast adoption in fabricating new biological molecules such as pyridines, quinolines, quinazolinones, imines, and their derivatives. This review covers the varied MOFs and their catalytic properties in facilitating the selective formation of the product organic moieties and interprets MOF’s property responsible for their elegant performance.